2015
DOI: 10.1080/13658816.2015.1065496
|View full text |Cite
|
Sign up to set email alerts
|

Movement analysis of free-grazing domestic ducks in Poyang Lake, China: a disease connection

Abstract: Previous work suggests domestic poultry are important contributors to the emergence and transmission of highly pathogenic avian influenza throughout Asia. In Poyang Lake, China, domestic duck production cycles are synchronized with arrival and departure of thousands of migratory wild birds in the area. During these periods, high densities of juvenile domestic ducks are in close proximity to migratory wild ducks, increasing the potential for the virus to be transmitted and subsequently disseminated via migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
(11 reference statements)
0
19
0
Order By: Relevance
“…APMV-1 outbreak reports often do not have details on the ecological environment in which the host bird was sampled making it unclear whether a duck is wild, domestic or feral and precluding the formal testing of this hypothesis with the dataset used in this investigation. As evidence exists that domestic and wild ducks often come into contact with one another when domestic ducks are allowed to browse freely [24], the barrier between these two groups may be porous in regions where there is spatiotemporal overlap of infected bird populations, particularly in production systems with low biosecurity. Furthermore, live bird markets may represent a distinct ecological niche that could produce limited cross-species transmission for APMV-1 due to the close proximity of multiple bird species and the constant turnover of naïve hosts.…”
Section: Discussionmentioning
confidence: 99%
“…APMV-1 outbreak reports often do not have details on the ecological environment in which the host bird was sampled making it unclear whether a duck is wild, domestic or feral and precluding the formal testing of this hypothesis with the dataset used in this investigation. As evidence exists that domestic and wild ducks often come into contact with one another when domestic ducks are allowed to browse freely [24], the barrier between these two groups may be porous in regions where there is spatiotemporal overlap of infected bird populations, particularly in production systems with low biosecurity. Furthermore, live bird markets may represent a distinct ecological niche that could produce limited cross-species transmission for APMV-1 due to the close proximity of multiple bird species and the constant turnover of naïve hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Eight migratory routes for wild birds exist in the world, and China is located in three of them: the East Asia–Australia Flyway, Central Asia Flyway, and the West Asia‐East Africa flyway. Lakes and related wetlands along the flyways (eg, Qinghai Lake Nature Reserve, Dongting Lake Nature Reserve, and Poyang Lake Nature Reserve) are very important staging, overwintering and breeding sites for migratory birds. Each migration season, tens of millions of wild birds (>10 million birds for Dongting Lake) congregate at the lakes, sharing a common habitat with local birds, including domestic ducks .…”
Section: Introductionmentioning
confidence: 99%
“…For a better understanding of how bird migration affects pathogen dispersal and infection prevalence dynamics, empirical studies such as tracking bird migration (Rappole et al 2000;Prosser et al 2009Prosser et al , 2016, analysing spatial and temporal correlation between bird movement and infection outbreak (Si et al 2009;, phylogenetic relationships among infection outbreaks (Tian et al 2015;Chen et al 2005) and theoretical modelling (Breban et al 2009;Rohani et al 2009) have been carried out.…”
Section: Migration Affects Pathogen Dynamicmentioning
confidence: 99%
“…Previous studies suggested that HPAIVs originated from domestic ducks, especially in environment with high densities and low bio-security when one co-infected with multiple subtypes of low pathogenic avian influenza viruses (LPAIVs) (Fearnley 2015;Takekawa et al 2010). Moreover, the domestic ducks are one of the main natural reservoirs of HPAIVs (Hill et al 2012) and their habitat facilitates virus persistence in the environment and transmission between hosts (Hénaux and Samuel 2011;Stallknecht et al 1990;Prosser et al 2016). Therefore, areas with high densities of domestic ducks, such as southeast China, are considered HPAIV outbreak hotspots (Prosser et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation